Strategy of the exit of the enterprise on the international commodity markets - Kanivets, Olena; Kolesnyk, Inna (Skhid, 2013)
In article the role of strategy of the enterprise in foreign trade activities has been defined and proved, practical recommendations concerning working out of strategy of an exit on the international commodity markets for the cake and by-product process are given the industry which are inherent for branch specialisation of east region.